Worksop Dapur Digitalpreneur: Memasak Ide, Menjual Lewat Internet - Khairunnisa Khairunnisa; Ali Riza Fahlevi; Nensi Damayanti (Community Service Progress, 2025)
This community service program partnered with the Rumah Kelor Anjani SME, a producer of healthy moringa-based processed foods in Bandung Regency. The partner faced two main challenges: (1) inaccurate calculations of the Cost of Goods Sold (COGS), which impacted profitability, and (2) a suboptimal digital marketing strategy for reaching a wider market. The implemented solutions included training in precise COGS calculations, product variant innovation, and Digital Business Strategy assistance, such as Instagram content optimization and marketplace management. As a result, the partner now has a profitable pricing structure and a measurable digital marketing roadmap to increase revenue and brand awareness in line with the Asta Cita (Downstreaming & Digital Economy) targets and SDG 8 (Decent Work and Economic Growth). The implemented solutions included training in precise COGS calculations, product variant innovation, and Digital Business Strategy assistance, such as Instagram content optimization and marketplace management. As a result, the partner now has a profitable pricing structure and a measurable digital marketing roadmap to increase revenue and brand awareness in line with the Asta Cita (Downstreaming & Digital Economy) targets and SDG 8 (Decent Work and Economic Growth).